Cibercultura e blogosfera: a significação dos blogs no jornalismo contemporâneo - Souza, Joyce da Silva (2010)
The main object of this research is the emergence of a new journalism practiced in the so-called blogosphere insofar as the socio-technical structure of production, information gathering, language, access, reception, distribution and reader participation is concerned. The work involved the analysis of blogs with common characteristics, i.e., allocation in Brazilian portals and media, written by journalists, and relevance in the blogosphere in terms of content and audience. The body of research comprises the following blogs: Noblat (O Globo); Josias de Souza (Folha de S. Paulo), Reinaldo Azevedo (Veja) and Luis Nassif Online (Brasilianas.org). The main objective here is to reflect on the changes in communication and in current journalism starting from the advent of the Internet and of blogs. The research problem consists in discovering if blogs actually contribute to this new journalism in their depiction of today s realities. The main authors underpinning the theoretical base of this work are David Harvey and Fredric Jameson, scholars of the transition from modernity to postmodernity; Paul Virilio, who addresses the phenomenon of speed and the war of time as characteristics of today s times; Manuel Castells, Nicholas Negroponte, Steven Johnson, Eugênio Trivinho and Pierre Lévy, who contribute conceptual elements for an understanding of the internet and of the relationship of individuals with this net; André Araújo, with respect to the culture of free software; Pollyana Ferrari, concerning the origin of the internet and of journalism in this context; Ricardo Nicola, also with regard to the origin of the internet and of several social networks; and Raquel Recuero, who examines the context of the individual and of virtual communities. The theoretical base is also strengthened by specialists in the theory of communication and journalism, who include Felipe Pena with his nuclear concepts of the profession (news, ethics, objectivity, etc.), and Nelson Traquina, one of the few authors dedicated to research into this professional practice and its identity, which is in continual transition. In this context, since 2000, structural changes are found in the forms of production and circulation of news, through which and from which the public is not only a receiver but has also become a generator of content. Based on the above, the hypotheses tested in this research lead to the following conclusions: 1) blogs are tools that contribute towards the aforementioned communicational changes in journalism; and 2) the professional, being his own editor and empowered by the freedom afforded by digital devices and networks, is in fact able to create his own language for the blogosphere. These conclusions indicate that a new journalism may be emerging through the internet and blogs, which today, in effect, is still a new arrangement of its old forms in the field of communication; but which, in the medium or long term, may give rise to important issues that will allow for a reassessment of the journalism practiced today